Creation and enforcement of inancial market law in the light of the economisation of law - Nieborak, Tomasz (Wydawnictwo Naukowe UAM, 2016)
This book raises some topical issues around the creation and enforcement of financial market law through the prism of the economisation of law. Its topicality arises from the fact that today when everyday life is becoming financialized, or in other words, when the financial sphere is gradually taking it over, the role of the legislator in shaping market relationships must be redefined. This means that the specificity of the matter regulated (i.e. the financial market) must be taken into consideration in the law-making process because this market constitutes an element of a greater whole which, apart from the financial and the economic system, consists of the social system as well. This thesis has been confirmed in recent years when the crises in financial markets have shaken the foundations of global society. Thus the legislator as an architect of the surrounding reality must take into account other factors as well, such as economic or psychological, and not just legal ones. This thesis can be found in earlier publications as well, for example in the work of Leon Petrażycki, but there has been no attempt as yet to transfer it to laws regulating the functioning of the financial market and which the behavioral concept of law would help us to understand. This concept may in the near future be regarded as a new paradigm of financial market law.
Keywords: prawo rynku finansowego; regulacja; proces oceny regulacji; ekonomizacja prawa; konsument; ekonomiczna analiza prawa